Entrevista com a professora Maria Adélia Aparecida de Souza - Maria Dolores Buss; Ewerton Vieira Machado; Luis Fernando Scheibe; Ivo Sostizzo; Sandra Maria de Arruda Furtado (Geosul)
Entrevista com a professora Maria Adélia Aparecida de Souza